Evaluation of mechanical properties of five cements for orthodontic band cementation - Diego Andrei Aguiar; Daltro Enéas Ritter; Roberto Rocha; Arno Locks; Adriano Ferreti Borgatto (Sociedade Brasileira de Pesquisa Odontológica, 2013)
The aim of this in vitro study was to compare the flexural, compressive and diametral tensile strengths of five cements used in orthodontics for band cementation. Twelve specimens of each cement were tested: 1 - GC Fuji Ortho Band (FJ), GC America Inc.; 2 - Meron (MR), Voco; 3 - Multi-Cure Glass Ionomer Band Cement (MC), 3M Unitek; 4 - Band-Lok (BL), Reliance Orthodontic Products; and 5 - Ketac Cem (KC), 3M ESPE. The results (mean) for diametral tensile strength were: 10.51 MPa (FJ), 9.60 MPa (MR), 20.04 MPa (MC), 42.80 MPa (BL), and 4.08 MPa (KC). The results for compressive strength were (in the same order): 64.50 MPa, 77.71 MPa, 94.21 MPa, 193.88 MPa, and 81.93 MPa. The results for flexural strength were (in the same order): 20.72 MPa, 25.84 MPa, 53.41 MPa, 137.41 MPa, and 20.50 MPa. The statistical analysis was performed by two-way ANOVA and Tukey tests with p-value £ 0.05. In terms of diametral tensile strength, BL showed the highest strength statistically, and MC, the second highest. In terms of compressive tensile strength, BL showed the highest strength statistically, and FJ did not attain the minimum recommended strength. In terms of flexural tensile strength, BL cement was superior to MC, and MR, FJ and KC were equivalent and inferior to BL and MC.